Microsatellite Analysis of Genetic Diversity in Pekin(Anas platyrhynchos) and Muscovy (Cairina moschata)Duck Populations - Ahmadi, A. Khan; Rahimi, G.; Vafaei, A.; Sayyazadeh, H. (International Journal of Poultry Science, 2007)
In the present study the genetic structure of Pekin and Moscovy duck populations in north of Iran, Mazandaran province were analyzed using thirteen microsatellite markers. One hundred blood samples with equal number from each population were collected and DNA was extracted using modified salting out method. After Polymerase Chain Reaction (PCR), the PCR products were electrophoresed using 6% polyacrylamide gel. Four Out of 12 microsatellite markers were not amplified in any of both populations, three markers were monomorph and six markers generated polymorph bands. Some genetic parameters such as observed and effective allele number, mean of heterozygosity and genetic distance between two duck populations were estimated. The observed allele number in each locus was ranged from 1-4, effective allele number from 1-3.78, heterozygosity from 0-0.98 and the genetic distance between two populations was measured as 0.59 percentages. The low of genetic distance between two populations and the low level of mean heterozygosity index indicate that the genetic diversity is low in within and between populations. The low mean heterozygosity may be attributed to the low number of alleles present in the population, high level of inbreeding values because of small effective population size involved in studied duck breeding flocks. The analysis of Hardy-Weinberg equilibrium test showed that none of the microsattelite sites were at equilibrium. The obtained results at the present study indicated that characterization of genetic diversity by employing molecular tools is a prerequisite in developing strategies for conservation and utilization of duck genetic resources.